Residual Effects of Organic Manure and Mineral Nutrients on Yield of Wheat and Nutrient Status of Soil in Cowpea-wheat Sequence - Sharma, S R; Bhandari, S C; Purohit, A K; Chippa, B R (Annals of Arid Zone, 2016)
The application of FYM and mineral nutrients to cowpea significantly increased the grain and straw yields of subsequent wheat crop. The interactive effects were significant for grain and straw yields or wheat. available nitrogen and iron for both the years and cobalt during 2000-2001 with highest values under the application of FYM @! 10 t hu-I -+- mineral nutrient combination. i.e .. @ 20. 1.0, 50, 25 and 0.5 kg ha:'( elemental sulphur. sodium molyhdate. ferrous sulphate. zinc sulphate and cobalt nitrate. respectively.